ANALISIS POTENSI EKOWISATA DANAU TOBA DI PANTAI PARIS KABUPATEN SIMALUNGUN SUMATERA UTARA (Analysis Potential Ecotourism Toba Lake in Paris Beach, Simalungun district, North Sumatera) - Putri Y R Simanjuntak; Pindi Patana; Tajuddin Siregar (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Toba Lake is one of tourism destination aim in North Sumatera Province. The research to know carrying capacity region Paris Beach tourism, conformity of environment as tourism and tourists perception to Paris Beach potention as one of tourism destination and alternative strategy for development tourism region. This research has been carried out in the Paris Beach Village of Tigaras, District of Dolok Pardamean, Regency of Simalungun on February 2017 by analyzing parameter of water quality as such water themperature, water brightness, current speed, pH, DO, BOD, and Total Coliform. The results are showed all parameters meet the water quality standards on PP No. 82 Tahun 2001. Paris Beach is classified very approviate as tourism region with tourism index 83. 33%. The alternative strategy to develope the tourisme is y conducting a good promotion to expose resources and potention of Paris Beach, region government and central government realization gevern plan of Danau Toba Toursm.Key word : corresponding tourism index, carrying capacity region, SWOT